If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-2x + 5) = -136 Reorder the terms: -8(5 + -2x) = -136 (5 * -8 + -2x * -8) = -136 (-40 + 16x) = -136 Solving -40 + 16x = -136 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 16x = -136 + 40 Combine like terms: -40 + 40 = 0 0 + 16x = -136 + 40 16x = -136 + 40 Combine like terms: -136 + 40 = -96 16x = -96 Divide each side by '16'. x = -6 Simplifying x = -6
| 2(-10-7x)=50 | | 2(5-1.7b)=15.1-7(1.7) | | 2v-3v+3-4v=0 | | (3x-5)(x-8)=0 | | 11+6y-8y=-3+3y | | 13x-4=7x-22 | | 48-32=4(12-x) | | -2gh(g^3h^5)=0 | | 7x+2=4x-9 | | 8b-8=-6(b-3)+6(1+2b) | | 12x-14=16x | | -(1+7x)-6(-7-x)=6 | | 7n-8+2+7n=0 | | -4(2+m)=2(m-7) | | 60y-108+12= | | Q+2=q+16 | | 12=1/3z+7 | | -4y^3-8xy^4=4y^3(1+2xy) | | 4y=5x+4 | | X-32=4(12-y) | | -6+4s=-2 | | 2u+4=16 | | 2(7x+3)=20 | | -2x+8x-7=6(x-4)-3 | | 0=3x^2-x-120 | | -6v+3v-9=-3 | | 4z+6=2z+6 | | -9=7(7v+8)+4(5v+1) | | 3(a-1)-5=34 | | 0.25(8z-4)=1z+8-2z | | 8-9+4b-5f= | | 4[5x-(2x-7)]=2(4x-5) |